Are you intended towards e-waste recycling?: a case of USM students / Muhamad Azfar Mohamad Zuhdi and Haziq Iskandar Hamdan - Mohamad Zuhdi, Muhamad Azfar; Hamdan, Haziq Iskandar (2019)
Nowadays, the proliferation of technological advancement in the electrical and electronic industry had led to the development of sophisticated devices which results in the increment of the obsolete rate of the lower device which tends to be waste electrical and electronic equipment (WEEE) (Sabbaghi, Esmaeilian, Raihanian, Behdad and Cade, 2015). Directing to the e-waste problem, this issue is a global concern as e-waste is a source for a load of toxic materials such as lead, cadmium, mercury, chromium and poly-brominated biphenyls. In addition, e-waste is a source of precious metals such as iron (Fe), copper (Cu), aluminium (Al), gold (Au), silver (Ag) and others (Madrigal-Arias et al, 2015). Furthermore, electronic waste contributed to the concentration of lead (Pb) to the landfills in the US (EPA, 2000).